A Rasch-based regression analysis of predictive relationships among mathematics motivation constructs - Alyani, Fitri; Nurafni; Hadi, Windia (Jurnal Elemen, 2026)
Mathematics motivation refers to students’ internal or external beliefs, values, emotions, and regulatory processes that drive their engagement and effort in learning mathematics. This study investigates the relationships among the constructs of mathematics motivation (intrinsic value, self-regulation, self-efficacy, utility value, and anxiety). The methodology of this research employs a quantitative approach (Rasch and partial t-test analyses), with 317 secondary school students in Jakarta, Indonesia, as respondents. The validation and reliability instruments were conducted using the Rasch model, and then the regression analysis and partial t-test analyses were used to examine predictive relationships among the motivational constructs. The results showed that self-efficacy is the most influential factor, significantly predicting intrinsic value, self-regulation, utility value, and anxiety test. Intrinsic value and utility value also contributed significantly to multiple motivational outcomes, while anxiety test was predicted by intrinsic value, self-efficacy, and utility value, but not by self-regulation. The findings provide theoretical evidence that self-efficacy functions as a central mechanism linking key dimensions of mathematics motivation, underscoring its important role in shaping students’ motivational profiles in mathematics learning contexts.